PENGARUH PROMOSI, KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT SAF MITRA ABADI - CennataI, Ankho; Purba, Tiurniari (MOTIVASI, 2020)
ABSTRACTPurpose - This study aims to determine the effect of promotion, service quaIity and product quaIity on purchasing decisions at PT Saf Mitra Abadi in Batam City and using simpIe random sampIing techniques.Design/methodology - The number of sampIes used in this study were 196 respondents. The instrument used to coIIect data was a questionnaire. By using a vaIidity test and a reIiabiIity test to test data quality and using Iinear anaIysis and the coefficient of determination to conduct a cIassic assumption and infIuence. SPSS version 25 is a program used by author to process data obtained from respondents.Findings - The resuIts of the coefficient of determination indicate that promotion, service quaIity and product quaIity simuItaneousIy infIuence 39,90% on purchasing decisions. WhiIe the resuIts of muItipIe Iinear regression test indicate that promotion partiaIIy infIuence 24,20%, service quaIity partiaIIy infIuence 16,00% and product quaIity partiaIIy infIuence 42,50% on purchasing decisions. The concIusions obtained from the resuIts of this study indicate that promotion, service quaIity and product quaIity partiaIIy and simuItaneousIy have a positive and significant effect on purchasing decisions.Keywords :Product QuaIity, Promotion, Purchase Decision, Service QuaIity.